DAMPAK PENGERUKAN PASIR TERHADAP KELIMPAHAN PLANKTON DAN KUALITAS AIR DI HULU DAERAH ALIRAN SUNGAI BELAWAN, KECAMATAN PANCUR BATU, KABUPATEN DELI SERDANG - Christina Sagala; Zulkifli Nasution; Yunasfi Djayus (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2013)
Watershed is the area bounded ridge where the rain water that falls on the area will be accommodated by the ridge and will be streamed through small streams to the main river. The presence of sand dredging activities in upstream watersheds Belawan can be lower water quality and abundance of micro-organisms, including plankton. This research had been conducted from April to July 2013 in Belawan Watershed Headwaters. This research used Purpossive Random Sampling methods. There were 2 stations, Station 1: Pertampilen village, District Pancur Batu as an active area of sand dredging activities, Station 2: Salam Tani village, District Pancur Batu as areas which were far away from the sand dredging activities. Sampling activities were conducted 4 times once/month. The research aimed to knew water quality and determined the abundance of plankton in Belawan Watershed Headwaters.The results showed that at the station I, there were found 19 genera of phytoplankton and 1 genera of zooplankton and at the station II, there were only found 17 genera of phytoplankton. Plankton abundance at the station I was 85, 404 ind/l and at station II was 128,684 ind/l. Water quality at the station I had passed the thresholds as water quality raw materials, such as ammonia and nitrite. Turbidity also have very high at station I. This research showed that the sand dredging activity affected the abudance of plankton in the river.Keywords: Water Quality, Sand Dredging, Plankton, River